Human Resources’ Strategic Initiatives in the Public Sector: An Explanatory Study - Papadopoulos, Antonios; Ozbag, Alexandros; Kyrgidou, Lida (International Conference on Business and Economics - Hellenic Open University, 2025)
Human Resource Management is crucial in contemporary business. This study explores attracting and retaining Generation Z within public sector entities, addressing several challenges such as demographic transition, digitalization, innovation, business performance, organizational culture, and sustainable competitive advantage, with particular emphasis placed on the co-existence of four generations in the workplace. Stuckey (2016) states that many leaders and managers lack the necessary insight to effectively manage the work needs and expectations of Generation Z compared to previous generations (Kupperschmidt, 2000). This study aims at identifying effective strategies to attract, recruit and most importantly, retain Generation Z, considering job retention factors of Generation Z individuals in the Federal State of Nordrhein-Westfalen in Germany, focusing on the town of Düsseldorf. A questionnaire served as the main survey instrument, with items adapted by previous related studies (e.g. Acheampong, 2019; Bos, 2021; Fodor & Jaeckel, 2022; Schnetzer, 2023; Wright, 2022). The questionnaire was distributed to a broad sample of individuals employed in or expressing interest in the public sector within the Federal State of Nordrhein-Westfalen. Based on the findings, the study suggests respective strategies to attract, recruit and retain Generation Z and provides implications to HR specialists, public sector managers and policy makers alike. JEL Classifications: M12, M51 Keywords: Retention strategies, Generation Z, Personnel Attraction, HRM Public Sector